Semantic Web-based information systems state-of-the-art applications - Sheth, A. (Amit) 1959-; Lytras, Miltiadis D. 1973- (Cybertech Pub., 2007)
"This book covers new semantic Web enabled tools for the citizen, learner, organization, and business. Real-world applications in development of the knowledge society and semantic Web issues, challenges and implications in each of the IS research streams are included as viable sources"-- Provided by publisher.